IMPLEMENTASI PROBLEM BASED LEARNING DAN LATIHAN TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA - Refka Alian; Stepanus Sahala Sitompul; Muhammad Musa Syarif Hidayatullah (Institut Pendidikan Tapanuli Selatan, 2022)
A preliminary survey conducted at SMK Negeri 7 Pontianak showed that the learning outcomes of students did not meet the basic school completeness criteria. The purpose of this study was to see whether the problem based learning model and guided exercises could help students majoring in welding engineering at SMK Negeri 7 Pontianak improve their learning outcomes. This study uses a quasi-experimental approach. The sample in this study were students of class X.A and X.B majoring in welding engineering at SMK Negeri 7 Pontianak in the academic year 2021/2022 with the sampling technique being intact group. The research data was obtained through pretest and posttest data and processed quantitatively. The results showed that both the experimental class and the control class there was an increase in learning outcomes. Learning outcomes in the experimental class increased from the class average of 24.86 to 82.40, with an N-gain value of 0.76 in the high category. While in the control class, there was an increase from the average class value of 26.31 to 77.97 with an N gain value of 0.69 in the medium category. Thus it can be concluded that improving learning outcomes is more effective with the implementation of problem based learning and guided exercises.